Clubfoot Versus Positional Foot Deformities on Prenatal Ultrasound Imaging. (2nd October 2019) - Brasseur‐Daudruy, Marie; Abu Amara, Saad; Ickowicz‐Onnient, Valentine; Touleimat, Salma; Verspyck, Eric
Abstract : Clubfoot and positional foot deformities (eg, pes spinatus) may have the same aspects on prenatal ultrasound (US) imaging. Nevertheless, differentiating these entities is essential because their prognoses are different. This pictorial review illustrates the US findings of clubfoot and positional foot deformities. On the basis of clinical postnatal images, we describe a prenatal US technique that could give an accurate diagnosis. In this essay, we demonstrate that when a foot malposition is suspected, a systematic analysis with 3 rigorous planes could help differentiate positional foot deformities from malformations and define their types.